PENERAPAN PRINSIP DUTY OF CARE OLEH DIREKSI PERSEROAN TERBATAS DI INDONESIA - Maristella, Debora; ', Firdaus; Bachtiar, Maryati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The board of directors shall be the organ of the company which is fully responsible for the management of the company for the purpose and represents the company either inside or outside the court in accordance with the basic provisions. The management of a limited liability company shall be carried out by every member of the board of directors in good faith and with full responsibility. In order to create a good thing then the board of directors must have what is called the fiduciary duty which is duty of care, it is an obligation for the directors to carry out their responsibilities carefully as a driver in the company, as the life in the company to can run the company continuously. Any member of the board of directors who is considered guilty of negligent in his/her duty shall be held personally liable on the basis of having no good faith and/or no sense of responsibility in performing duties for the interest and business of the company.The purpose of writing this thesis that is, First, to know arrangement about principle of duty of care in Indonesia. Second, to know benchmark of a directors can be assumed not to implement duty of care principle.This type of research is normative legal research or can be called also research doctrinal law. From the results of research problems, there are two main points that are concluded, first, the regulation of the principle of duty of care in Indonesia. Second, the benchmark of a board of directors may be suspected not to implement the principle of duty of care.Keywords : Board of directors, duty of care